Musculoskeletal Tuberculosis Involving Ribs, Spine, and Pelvis in a 17-year-old Girl: A Case Report - Hammoud, Lina; Neaimeh, Yara; El Taoum, Katia; Zakhour, Ramia (International Journal of Clinical Research, 2022)
Background: We present a case of progressive back pain associated with weight loss and low-grade fever in a 17-year-old patient previously diagnosed with spinal tuberculosis (TB) also known as tuberculous spondylitis or Pott’s disease. Case presentation: Upon the patient's presentation to the clinic, a differential diagnosis including infectious and non-infectious causes such as extra-pulmonary tuberculosis, septic arthritis, malignancy, rheumatologic diseases, and physical abuse was made. Her preliminary workup was suggestive of granulomatous disease. A positive tuberculin skin test (TST), and a polymerase chain reaction (PCR) test of the tissue with mycobacterium tuberculosis deoxyribonucleic acid (MTB DNA), confirmed the diagnosis of musculoskeletal TB. Conclusion: The patient was treated with anti-TB regimen and Pyridoxine to avoid peripheral neuropathy associated with isoniazid use. Her clinical follow-up showed improvement with a proper response to treatment and no sequelae.